2009
DOI: 10.1136/jnnp.2009.174276
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cell stress in sporadic inclusion body myositis muscle: overexpression of  B-crystallin is associated with amyloid precursor protein and accumulation of  -amyloid

Abstract: Our results suggest that alphaB-crystallin is associated with overexpression of APP in sIBM muscle and that upregulation of alphaB-crystallin precedes accumulation of beta-amyloid. The data help to better understand early pathological changes and underscore the fact that a network of cell stress, inflammation and degeneration is relevant to sIBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 18 publications
2
31
1
4
Order By: Relevance
“…A similar relationship, possibly mediated by the GSK-3b kinase, has been demonstrated in an animal model of the disease [10]. Apart from inflammation, an early cell stress response around aB-crystallin and nitric oxide is present in IBM muscle and may precede accumulation of b-amyloid [9,11]. The cytokines IFN-c and IL-1b have been demonstrated to be key inducers of accumulation of b-amyloid in muscle cells.…”
Section: Immunological Studiesmentioning
confidence: 82%
“…A similar relationship, possibly mediated by the GSK-3b kinase, has been demonstrated in an animal model of the disease [10]. Apart from inflammation, an early cell stress response around aB-crystallin and nitric oxide is present in IBM muscle and may precede accumulation of b-amyloid [9,11]. The cytokines IFN-c and IL-1b have been demonstrated to be key inducers of accumulation of b-amyloid in muscle cells.…”
Section: Immunological Studiesmentioning
confidence: 82%
“…It appears therefore that, aB-crystallin may be an early event associated with a stress-response that precedes accumulation of b-amyloid. This view was further supported by in vitro studies which demonstrated that accumulation of b-amyloid, upon pro-inflammatory cell-stress, was preceded by upregulation of APP and aB-crystallin [103]. The noted cross-talk between inflammation and degeneration, although does not provide any information on what is the primary event, argues that inflammation may enhance the protein misfolding process.…”
Section: Interrelationship Between Inflammation and Amyloid Or Stressmentioning
confidence: 84%
“…aB-crystallin had been immunolocalized to healthy-appearing muscle fibers in IBM muscle almost a decade ago [102]. In a current quantitative assessment of multi-labeling and serial immunohistochemistry, a positive correlation between aB-crystallin and bamyloid-associated markers was found in sIBM muscles [103]. The normal-appearing muscle fibers that were positive for aBcrystallin were often double-positive for APP, while APP/bamyloid co-localized with markers of cell-stress and regeneration/degeneration.…”
Section: Interrelationship Between Inflammation and Amyloid Or Stressmentioning
confidence: 97%
“…These muscle fibres have been referred to as "X fibres", since it was assumed that they carry a very early pathological change, which would become manifest over time in the form of changes in cell structure, such as vacuoles for example. In a recently published work, our group was able to shown that αB-crystalline und β-amyloid correlate significantly with one another [16]. In particular, so-called "X fibres" were often positive for APP or even β-amyloid, which could also be shown together with other markers for regeneration or degeneration, such as NCAM or desmin in the same fibre.…”
Section: Cell Stress Mechanismsmentioning
confidence: 93%